If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -8 + 5x = 12x + 24 Reorder the terms: -8 + 15x + 5x = 12x + 24 Combine like terms: 15x + 5x = 20x -8 + 20x = 12x + 24 Reorder the terms: -8 + 20x = 24 + 12x Solving -8 + 20x = 24 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -8 + 20x + -12x = 24 + 12x + -12x Combine like terms: 20x + -12x = 8x -8 + 8x = 24 + 12x + -12x Combine like terms: 12x + -12x = 0 -8 + 8x = 24 + 0 -8 + 8x = 24 Add '8' to each side of the equation. -8 + 8 + 8x = 24 + 8 Combine like terms: -8 + 8 = 0 0 + 8x = 24 + 8 8x = 24 + 8 Combine like terms: 24 + 8 = 32 8x = 32 Divide each side by '8'. x = 4 Simplifying x = 4
| 7x-2=6x-2 | | 3(4a+6)=114 | | log[2]*(3x-1)=5 | | 0.8(5x-1000)+1.3=2.9-x | | 7(6-5v)=252 | | 7(6-5v)=525 | | 80=6x+30 | | -7(-2m+7)=-147 | | t-11=23 | | -152=4(4n-8)-8 | | (2x-3y)= | | log[4]*5x+log[4]*3y= | | -3(1+5n)=87 | | 120=-8(n-8) | | 2x+8(4x+1)=-196 | | n+13=13 | | 7(5+4x)=-105 | | -98=2(2n-7)+8n | | m=3m^2-2 | | 3(7m+5)=-90 | | 3(4x+7)-1=5-(2x-3) | | 5(3)-6=9 | | h(3x-1)=2/3(3x-1)-5 | | 6+2(x+8)= | | h(5/2)=2/3×(5/2)-5 | | 3x/8=12/5 | | 2x/3-x/4=1/2 | | 11(y+3)=44 | | h(-1)=2/3x(-1)-5 | | ln(4x-8)=0 | | 4x-3x=10-12 | | 2(x+5)=3(3x+3) |